2005
DOI: 10.1021/jp052112o
|View full text |Cite
|
Sign up to set email alerts
|

Nucleophilic Substitution Reactions at Liquid/Liquid Interfaces:  Molecular Dynamics Simulation of a Model SN1 Dissociation Reaction at the Water/Carbon Tetrachloride Interface

Abstract: The ionic dissociation step of the nucleophilic substitution reaction t-BuCl --> t-Bu(+) + Cl(-) is studied at the water/carbon tetrachloride interface using molecular dynamics computer simulations. The empirical valence bond approach is used to couple two diabatic states, covalent and ionic, in the electronically adiabatic limit. The umbrella sampling technique is used to calculate the potential of mean force along the reaction coordinate (defined as the t-Bu to Cl distance) at several interface regions of va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 56 publications
0
19
0
Order By: Relevance
“…To circumvent this problem, several methods providing enhanced sampling of rare events, such as harmonic and adaptive umbrella sampling, thermodynamic integration, metadynamics, , the Widom test particle insertion method and its cavity insertion variant, or potential of mean force (PMF) calculation by, for example, constrained molecular dynamics, , have been proposed over the years. These methods of solvation free energy calculation have been applied for a number of ionic and nonionic penetrants , at various fluid interfaces in the past decades, complementing theoretical predictions based on various continuum dielectric calculations. , …”
Section: Introductionmentioning
confidence: 99%
“…To circumvent this problem, several methods providing enhanced sampling of rare events, such as harmonic and adaptive umbrella sampling, thermodynamic integration, metadynamics, , the Widom test particle insertion method and its cavity insertion variant, or potential of mean force (PMF) calculation by, for example, constrained molecular dynamics, , have been proposed over the years. These methods of solvation free energy calculation have been applied for a number of ionic and nonionic penetrants , at various fluid interfaces in the past decades, complementing theoretical predictions based on various continuum dielectric calculations. , …”
Section: Introductionmentioning
confidence: 99%
“…Computer simulation techniques, such as molecular dynamics or Monte Carlo, are handy tools to provide us with an in-depth molecular level picture of our systems of interest. Bearing such advantages, these methods have recently been widely used to investigate the behavior of different ions both at the liquid/vapor interface of their solutions and at liquid/liquid interfaces formed by the aqueous ionic solution and various organic compounds immiscible with the aqueous phase. Some of these computational studies address directly the question of ionic distribution in the interface normal direction by placing a number of ions into the aqueous phase and calculating their density distribution from the resulting trajectory . Such studies showed that only the compact monatomic ions characterized by low polarizability (e.g., F – ) obey the original theory of Onsager and Samaras .…”
Section: Introductionmentioning
confidence: 99%
“…Some papers are of more relevance to phase‐transfer catalysis 36. 37 Concerning the hydroformylation of olefins, we recently reported an exploratory MD study of biphasic solutions of the main species of the reaction and these were found to be surface‐active. Furthermore, a complex formed between a native cyclodextrin and the key reaction intermediate [RhH(CO)(TPPTS) 2 (decene)] 6− was also adsorbed at the interface 38.…”
Section: Introductionmentioning
confidence: 99%